Audit Teknologi Informasi Menggunakan COBIT 5 Domain DSS Pada Universitas Stikubank Semarang - Daffa Iqbal Agselmora; Agus Prasetyo Utomo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Today's technology has become an important part of people's daily activities. All lines of fields are competing to create an information system that is useful to meet needs in achieving its goals. Included in the realm of education, especially in higher education in Indonesia. Universities began to slowly implement information technology-based systems to facilitate all administrative activities on campus. COBIT 5 is a framework that is intended to help organizations meet their goals and create optimal value in managing the governance of information technology. The purpose of this research is to audit the information technology governance of the smart campus system of the stikubank university in Semarang using the COBIT 5 framework to determine the level of asset security and encourage the achievement of organizational goals effectively. The results of the research on the smart campus information system audit at Stikubamk University Semarang reached a value of 3.89 in the maturity level process, which means the process only reached level 3, while the capability level process only reached level 2. upgrade to the next level.